Methodological proposal for evaluation of the pedaling technique of cyclists: a case study - Diefenthaeler, F.; Bini, R. R.; Nabinger, E.; Laitano, O.; Pivetta Carpes, F.; Bolli Mota, C.; Stringhini Guimaraes, A. C. (Revista Brasileira de Medicina do Esporte, 2008)
Many techniques have been used in biomechanics to describe the cycling movement. The purpose of this study is to proposal a specific methodology to evaluation the forces applied on the pedal. An experienced elite cyclist was submitted to a protocol which consisted of four different saddle positions (upward, downward, forward, and backward) assuming as reference position the one used by the cyclist in training and competition. The displacement of the saddle was of 1cm in all tests. The individual's bicycle was connected to a magnetic cycle simulator. The load was normalized by a physiological criterion (ventilatory threshold), to simulate the cyclist's race rhythm. The right regular pedal was replaced by a 2D instrumented pedal to record the force normal and tangential components applied on it. Mean impulse of the angular effective force was calculated from ten consecutive pedaling cycles. The four different saddle positions have modified the effective angular pedaling impulse comparing with the reference position. Relatively small saddle adjustments may affect the effective angular pedaling impulse and supposedly cycling performance.